Lymphocyte‐activation gene‐3, an important immune checkpoint in cancer. Issue 9 (25th August 2016) - He, Yayi; Rivard, Christopher J.; Rozeboom, Leslie; Yu, Hui; Ellison, Kim; Kowalewski, Ashley; Zhou, Caicun; Hirsch, Fred R.
Abstract : Immunotherapy has recently become widely used in lung cancer. Many oncologists are focused on cytotoxic T lymphocyte antigen‐4 (CTLA‐4), programmed cell death ligand‐1 (PD‐L1) and programmed cell death‐1 (PD‐1). Immunotherapy targeting the PD‐1/PD‐L1 checkpoints has shown promising efficacy in non‐small cell lung cancer (NSCLC), but questions remain to be answered. Among them is whether the simultaneous inhibition of other checkpoints could improve outcomes. Lymphocyte‐activation gene‐3 (LAG‐3) is another vital checkpoint that may have a synergistic interaction with PD‐1/PD‐L1. Here we review the LAG‐3 function in cancer, clinical trials with agents targeting LAG‐3 and the correlation of LAG‐3 with other checkpoints. Abstract : Immunotherapy in cancer is a hot topic and many oncologists want to learn about the relevant biomarkers with the current focus on CTLA 4 and PD 1/PD L1. However, also of interests are the varieties of alternative immune checkpoints including Lag 3/MHC II. In this paper, we review LAG 3 structure, function, the synergistic effects with CTLA 4 and PD 1/PD L1, as well as discussing LAG 3 clinical trials which are ongoing.